Clinical Experience Using a Real Time Autofluorescence Endoscopy System in the Gastrointestinal Tract. Issue 2 (1999) - Ogihara, Tatsuo; Watanabe, Haruo; Namihisa, Akihiro; Kobayashi, Osamu; Miwa, Hiroto; Sato, Nobuhiro
Abstract : Autofluorescence spectra of neoplastic tissues have been reported to be significantly different from those of normal tissues when excited by blue or violet light. From this concept, a light-induced autofluorescence endoscopic imaging system for gastrointestinal mucosa (LIFE-GI; Xillix, Canada and Olympus, Japan) has been newly developed and the clinical evaluation of the prototype system has been conducted in hospitals in Canada, Netherlands and Japan. We examined the clinical usefulness of the prototype LIFE-GI system for the detection of gastrointestinal cancer and high and low grade dysplasia. The LIFE-GI system was also applied to the early detection of remnant lesions after endoscopic treatment of early gastric cancer and to the detection of laterally spreading superficial colonic tumors. This system has potential application for the diagnosis of dysplastic lesions and early cancers in the gastrointestinal tract as an adjunct to ordinary white light endoscopy. This system, which needs no administration of a photosensitive agent, may be suitable as a screening method for the early detection of neoplastic tissues.